KAUSALITAS ANTARA ANXIETY, SOCIAL PHOBIA TERHADAP PEMAIN VIDEO GAME - RIADI, ALEXANDER JOSEPH; SUKARSA, I KOMANG GDE; SUCIPTAWATI, NI LUH PUTU; KENCANA, EKA N.; SUSILAWATI, MADE; GANDHIADI, G.K. (E-Jurnal Matematika; Vol 13 No 1 (2024)DO - 10.24843/MTK.2024.v13.i01.p437, 2024)
Life satisfaction is one of the most ambigious concept to take a hold on. One’s degree of life satisfaction can differ from other person even though they have a realtively similliar life. This research studies people who play video games regularly (gamers) from the age of eighteen to fifty six. As one of the common trait or stereotipically seen that gamers have difficulty in social aspect of their lifes. Using Structural Equation Modeling (SEM), the research will try to confirm the relationship between anxiety and social phobia toward life satisfaction. The final model shows that anxiety and social phobia shows a significant negative affect towards life satisfaction of gamers.